IMAGING STUDIES: A WINDOW INTO NEWBORN'S BRAIN STRUCTURAL ABNORMALITIES AND ACQUIRED INJURY - Aneta Soltirovska Šalamon (The Society for Children with Metabolic Disorders, 2024)
Neuroimaging is not just a theoretical concept but a practical tool central to neonates' evaluation, treatment planning, and prognostic assessment. The sophistication and potential imaging data from standard and emerging neuroimaging techniques have expanded significantly over the last 40 years. Significant advances in neuroimaging have been made during this time frame regarding improvements in neonatal clinical care and the fundamental scientific discoveries that have been foundational for these improvements. Application of these techniques to the neonatal population is now a virtual constant in regular clinical neonatal practice and in investigative studies designed to facilitate an improved understanding of disease pathophysiology and the development and validation of potential new therapies. The present manuscript discusses the role of imaging methods and their findings in the diagnosis and prognosis of various acquired and congenital lesions in term and premature newborns.